Gain pondéral gestationnel et issue de l’accouchement chez les parturientes au Kasaï-Oriental « Etude menée dans les zones de santé de Bonzola et Kansele dans la ville de Mbuji Mayi » (REVUE DES SCIENCES DE LA SANTE, 2025)
This study aimed to verify the relationship between gestational weight gain and delivery outcomes among women in labor in the Bonzola and Kansele health zones of Mbuji-Mayi. We conducted a descriptive, analytical cross-sectional study using G-POWER software. The results showed that the majority (79.8%) of women had insufficient weight gain compared to the norm. Pregnant women with insufficient gestational weight gain are associated with adverse maternal outcomes, either through non-term pregnancy (OR.aj = 25.290, 95% CI [4.529-141.208], p=0.000) or prolonged labor (OR.aj = 8.4, [4.2-16.91], p=0.000). The results also revealed that insufficient gestational weight gain weakly influences an adverse neonatal outcome of delivery by premature birth (OR.aj = 0.079, [95% CI = 0.013-0.504], p = 0.007) and significantly influences the size at birth of the newborn (OR.aj = 3.862, [95% CI = 1.136-13.125], p = 0.030). While pregnant women with excessive gestational weight gain would lead to an unfavorable paternal outcome either by premature rupture of membranes (OR.aj = 110.31, [95% CI = 2.792-4357.5], p = 0.012) and dystocic delivery (OR.aj = 27.46, [95% CI = 1.073-703.116], p =0.045).
Keywords: Gain; weight; management; delivery outcome; parturient